Competing Priorities : Women's Microenterprises and Household Relationships - Friedson-Ridenour, Sophia; Pierotti, Rachael S. (World Bank, Washington, DC, 2018)
Recent studies have suggested that women's business decisions are influenced by members of their household, especially their spouse, and that these intrahousehold dynamics contribute to gender gaps in entrepreneurship outcomes. This in-depth qualitative study among microentrepreneurs in urban Ghana sought to understand the connections between women's businesses and their households' management of economic resources. The findings show that women’s business decisions are influenced by: (1) a desire to reinforce their partner's responsibilities as a primary provider, (2) attempts to fulfill normative expectations regarding daily provision of needs for the family, and (3) a need to prepare for long-term security. To reinforce their husband's responsibilities as a provider, women hid income and savings, and sometimes explicitly limited business growth. To ensure their ability to smooth household consumption and respond to emergencies, women prioritized savings over investment. And, to plan for their long-term security, women opted for cautious business investment, maintaining pressure on their partner to meet current needs and investing in children and property for the future. More broadly, the findings illustrate that interpersonal interactions concerning the management of economic resources are an integral part of how household members negotiate their rights and responsibilities in relation to each other.